IMPROVING STUDENT EXCEPTION AND LEARNING OUTCOMES THROUGH A SUMMARY STRATEGY (CHILDREN EDUCATION MATERIALS IN SD) - St Aisyah (Universitas Lambung Mangkurat, 2021)
The final condition expected after the implementation of the research is that as many as 80% of students complete the material as seen from the suitability of the summary results with the aim of tutorial activities, and the average score of students when working on mandatory tutorial 2 and tutorial 3 mandatory assignments has an average increase of more than 3 In the first cycle, the number of students who completed the material was only 6 people or 50%. This means that there are still 50% of students who have not finished the material because the results of the summaries made are not by the learning objectives. In the second cycle, the number of students who completed the material increased to 83.33% or 10 students, which means that there was an increase of 33.33%. In the implementation of the mandatory tutorial assignment (TT2) assessment, class VIII A students obtained sufficient average scores satisfactorily is 82, 07 when compared with the average result of the 3 tutorial compulsory assignment assessment, namely 85.17. Although the average TT3 results are not too high, the difference in value is quite fantastic, namely 3.10, more than 3. This means that student learning outcomes seen from the average value of mandatory tutorial assignments have increased and met the performance indicators set.